Influence of the Chemical Composition of Asphalt and the 3D Morphology of the Aggregate on Contact Surface Adhesion - Luoke Li; Meng Guo; Cong Zeng (Advances in Civil Engineering)
The influence of the chemical composition of asphalt, the aggregate lithology, and the morphological characteristics of the aggregate on the level of adhesion between the asphalt and the aggregate is investigated. A contactless three-dimensional (3D) white-light scanning technique is used to obtain point cloud data of the aggregate particles. Six independent feature parameters are used as evaluation indices to quantitatively describe the multilevel features of the 3D morphology of road aggregates. Methods for analyzing the feature parameters based on the point cloud data of the aggregate are presented. Subsequently, the process and evaluation standard of the adhesion test are improved to quantify the spalling degree of the asphalt film on the aggregate surface under boiling conditions. The influences of the chemical composition of the asphalt and the aggregate morphology on the level of adhesion between the asphalt and aggregate are analyzed, and the compatibility between aggregates with different lithologies and the asphalt is assessed. The results show that the shape factor (SF) can be used to characterize the needle-flake shape of the particles, the ellipsoid index (E) is suitable to determine the angularity of the aggregate particles, and the 3D joint roughness coefficient (JRC3D) describes the roughness of the particle surface. The type of adhesion between the aggregate and the asphalt includes chemical and physical adsorption; chemical bonding is relatively strong, and the physical orientation force and mechanical interlocking force are relatively weak. Alkaline limestone aggregates should be used with asphalt with a high aggregate content of colloid and asphaltenes. Basalt aggregate with weak alkalinity should be used with asphalt with a high colloid content, and the use of angular aggregates should be avoided. Acidic aggregates with compact shapes, few edges and corners, and rough surfaces should be used prudently.